Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025599
|View full text |Cite
|
Sign up to set email alerts
|

Toward Everyday Gaze Input

Abstract: For eye tracking to become a ubiquitous part of our everyday interaction with computers, we first need to understand its limitations outside rigorously controlled labs, and develop robust applications that can be used by a broad range of users and in various environments. Toward this end, we collected eye tracking data from 80 people in a calibration-style task, using two different trackers in two lighting conditions. We found that accuracy and precision can vary between users and targets more than six-fold, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(60 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…The eye tracker was carefully calibrated before each session to ensure the binocular tracking performance. The accuracy of this eye tracker is around 0.6° and 0.9° in the x-and ydirection, respectively, and its precisions in both direction are around 0.9° (Feit et al, 2017). A post-experiment interview confirmed that participants were able to fully focus on the visual target in the non-math sections, and 8 that the mental arithmetic required much cognitive effort.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…The eye tracker was carefully calibrated before each session to ensure the binocular tracking performance. The accuracy of this eye tracker is around 0.6° and 0.9° in the x-and ydirection, respectively, and its precisions in both direction are around 0.9° (Feit et al, 2017). A post-experiment interview confirmed that participants were able to fully focus on the visual target in the non-math sections, and 8 that the mental arithmetic required much cognitive effort.…”
Section: Methodsmentioning
confidence: 73%
“…This attempt alleviates the constraint of the expensive research-grade eye tracker as pointed out by Bixler and D'Mello (2016). Although EyeX gives a similar accuracy (offset from the true gaze point) as Tobii Pro X2-60 as well as a reasonable precision (Feit et al, 2017) and its firmware is optimized for real-time interaction (Tobii AB, 2018), its frame rate still limits the accurate detection of some saccadic behaviours. This might affect our comparison of using the "classic" eye movement features, but it is currently unavoidable as research-grade eye trackers are too expensive for home-use intelligent interfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third area of work is the study of the variability in the data obtained from medium-to low-cost eye trackers in field conditions. This is in anticipation of widespread use of gaze position as an additional input channel in the context of personal computing, e.g., (Feit et al, 2017).…”
Section: Previous Workmentioning
confidence: 99%
“…Reingold addresses the measurement of data quality with two methods based on an artificial eye so that the same stimulus is presented to different eye trackers for the purposes of performance comparison. Feit et al (2017) investigated the variability in data quality in a study of 80 people using two remote eye trackers in two conditions representing differences in ambient lighting conditions. One condition was intended to represent natural light and the other artificial light.…”
Section: Data Quality and Unrestrained Usementioning
confidence: 99%